Tingkat Keberhasilan Tanaman Rehabilitasi Hutan dan Lahan (RHL) Tahun Pelaksanaan 2019-2021 di Desa Butang Kecamatan Mappak Kabupaten Tana Toraja - Barrung, Retwin; Ramli, Muhammad Agusfartham; Idris, Andi Irmayanti; Adhisty, Widyanti Utami; Semu, Yulsan Demma; Sarif, Muhammad (Pangale Journal of Forestry and Environment, 2025)
Forest and land rehabilitation someone is important effort to restore degraded forest ecosystems and improve land functions to support environmental sustainability and community well-being. This study's objective was to assess the effectiveness of forest and land rehabilitation (FLR) activities carried out between 2019 and 2021 in Butang Village, Mappak District, Tana Toraja Regency. The assessment is conducted by measuring plant growth percentage, plant height, and plant condition, and identifying factors that influence the success of FLR activities. This study was carried out from July to September 2024 in the BPDAS Jenenberang Saddang FLR work area in Butang Village, Mappak District, Tana Toraja Regency. The methods used include 4x4 plot measurements, field measurements, and questionnaires with the surrounding community. The results of the study showed that plant growth reached 79.54% of the total 1,000 seedlings/ha planted, with plant heights ranging from 5.1 to 5.8 meters after three years. All plants observed were in healthy condition. The success of RHL at this location is influenced by soil conditions, the selection of appropriate plant types, climate, planting and maintenance techniques, and active community participation. Based on these results, RHL activities in Butang Village were declared successful.